2018
DOI: 10.1080/08941939.2018.1447619
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Hemostatic Agents: A Comparative Evaluation of Two Gelatin/Thrombin-Based Hemostatic Matrices in a Porcine Kidney Surgical Model

Abstract: In a severe, high-volume bleeding model, residual bleeding at 2 minutes was significantly lower with SmGM versus StGM, and SmGM showed greater consistency across bleeding intensities. These findings may be attributable to dry mass per unit volume and/or ultrastructural differences between the two agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Another study investigating the hemostatic effect of microporous polysaccharide hemospheres on pigs that undergone partial nephrectomy reported the mean hemostasis time as 4,67 minutes for the experimental groups (33). A study comparing two different hemostats on porcine kidney surgical models demonstrated that blood loss decreased similarly after two minutes, however bleeding continued with decreasing rates for the next ten minutes (34). Bang et al in-vestigated the effects of hemostatic powder on acute gastric bleeding in porcine models and evaluated the lesion sites at 6, 18, 42, 66 hours after the application.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigating the hemostatic effect of microporous polysaccharide hemospheres on pigs that undergone partial nephrectomy reported the mean hemostasis time as 4,67 minutes for the experimental groups (33). A study comparing two different hemostats on porcine kidney surgical models demonstrated that blood loss decreased similarly after two minutes, however bleeding continued with decreasing rates for the next ten minutes (34). Bang et al in-vestigated the effects of hemostatic powder on acute gastric bleeding in porcine models and evaluated the lesion sites at 6, 18, 42, 66 hours after the application.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high cost associated with blood transfusion and its impact on hospital resources, the use of effective hemostats may be associated with potential cost savings due to reductions in transfusions. [23][24] Although our study did not include a formal cost-utility and cost-e cacy analysis, we applied equal volumes (5 ml) in the two groups to increase comparability. In a tertiary-care hospital, CHM costs 40 USD per 1 ml, and GHM costs 80 USD per 1 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high cost associated with blood transfusion and its impact on hospital resources, the use of effective hemostats may be associated with potential cost savings due to reductions in transfusions. [22][23] Although our study did not include a formal cost-utility and cost-e cacy analysis, we applied equal volumes (5 ml) in the two groups to increase comparability. In a tertiary-care hospital, CHM costs 40 USD per 1 ml, and GHM costs 80 USD per 1 ml.…”
Section: Discussionmentioning
confidence: 99%